The Impact of Debt-Equity Mixture on Profitability: Analysis of Selected Companies - Dr. Kanubhai Jeshingbhai Chaudhary (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The study examines the effects of debt-equity on the profitability of Cipla Ltd. and Dr. Reddy's laboratories, two well-known pharmaceutical companies’ data for the period of 2017-18 to 2021-22. The significance of comprehending how the ratio of debt to equity in a company’s capital structure affects its profitability serves as the driving force behind this study. The analysis includes key ratios of profitability and debt-equity including Return on shareholders’ funds, return on assets, and net profit margin, to comprehensively evaluate the relationship between the debt-equity mix and the profitability of the selected companies. The conclusions offer businesses insightful guidance for their financial decision-making processes and might lay the groundwork for additional study in the area. It also offers potential implications for optimizing their capital structure to increase profitability in a cutthroat market environment. As a result, it is found that there is a negative and not a statistically significant correlation between DER and Profitability ratio.